Effective regulatory institutions: The regulator's role in the policy process, including issues of regulatory independence - Tom Winsor (Organisation for Economic Co-operation and Development (OECD), Joint Transport Research Centre (JTRC), 2010)
This paper discusses three connected aspects of regulation: (1) what makes a regulatory authority effective; (2) what is the legitimate role of a regulatory authority in the making and implementation of policy, and how that role may be regarded by others, and (3) the issue of independence of regulation from undue political intervention. It argues that regulators are usually established to carry out complex technical tasks which government is unable or unwilling to do, partly because government wishes to distance itself from responsibility for some decisions, but, having invested regulatory authorities with sometimes considerable powers which are more detailed and intrusive than any possessed by government over state-owned entities or industries, political or bureaucratic impatience or intolerance of that power sometimes takes over, and undue governmental pressure or interventions follow. These interventions come about either because of regulatory failures, or because politicians wish themselves to exercise regulatory powers which they regret having transferred to regulatory authorities. Regulatory independence from political intervention and regulatory freedom from political considerations is internationally recognised as an important facet of effective economic regulation, but despite that, it can come under such severe pressure that the system will fracture, causing severe loss of confidence in the regulatory system and in the reputation of the host government for fairness and respect for the integrity of the systems of checks and balances which has been established for the protection of investment. It argues that regulatory independence is as much about regulatory behaviour and legal status.
Keywords: 330